Interaction of berberine, palmatine, coralyne, and sanguinarine to quadruplex DNA: A comparative spectroscopic and calorimetric study - Bhadra, Kakali; Kumar, Gopinatha Suresh (Biochimica et biophysica acta, 2011)
BACKGROUND: Interaction of isoquinoline alkaloids berberine, palmatine, coralyne and sanguinarine with human telomeric quadruplex DNA, dAGGG(TTAGGG)₃, has been investigated and compared with ethidium. METHODS: Biophysical techniques such as absorption, fluorescence, circular dichroism, optical melting and microcalorimetry have been used. RESULTS: Absorption and fluorescence studies revealed noncooperative 1:1 binding for all the molecules. Coralyne showed highest affinity (10⁶ M⁻¹) and for others it was ~10⁵ M⁻¹. The binding affinity varied as coralyne>sanguinarine>berberine>palmatine. Ethidium showed affinity close to sanguinarine. Comparative fluorescence quenching and polarization anisotropy of the emission spectra gave evidence for a stronger stacking interaction of coralyne and sanguinarine compared to berberine and palmatine. Circular dichroic spectral perturbations were similar in all the cases, but a strong induced circular dichroism for the bound molecules was observed only for coralyne and sanguinarine. The interaction of all the alkaloids was exothermic. Binding of coralyne and sanguinarine was predominantly enthalpy driven while that of berberine and palmatine was entropy driven. Heat capacity values of −169, −198, −105 and −95cal/molK, respectively, for coralyne, sanguinarine, berberine, and palmatine suggested significant differences in the hydrophobic contribution to the binding. CONCLUSIONS: This study presents a complete structural and thermodynamic profile of the binding of isoquinoline alkaloids with G-quadruplex. GENERAL SIGNIFICANCE: These results suggest strong and specific binding of these molecules to the G-quadruplex and highlight the differences in their structure in the interaction profile.